Factors influencing the attendance of preterm infants to neonatal follow up and early intervention services following discharge from NICU during first year of life in Iran - ravarian, aida; vameghi, roshanak; heidarzadeh, mohammad; nariman, shahin; sagheb, setareh; noori, fariba; ershadi, farhoud saeed; noroozi, mehdi (Iranian Journal of Child Neurology, 2018)
Abstract Purpose: Determining maternal and infantile factors associated with the number of attending times of preterm infants to Neonatal Follow up and Early Intervention services during one year after discharge from neonatal intensive care unit. Method: This study used data from a cohort of preterm infants born in Arash Women’s Hospital and consecutively admitted to the NICU at the same hospital from April 2014 to February 2015. Data was gathered by completing a questionnaire administered via phone. Data included mother’s age, education, type of pregnancy, history of abortion, history of premature birth, self-reported post-partum depression and the number of children, as well as infant’s gender, birth weight, gestational age, length of stay in the NICU, living area, twin or triplet birth, number of siblings, and the child rank. Number of attending times to services was recorded. Result: After multivariate analysis, shorter length of stay in the NICU, lower maternal education, more number of children, self-declared lack of awareness about Neonatal Follow up and Early Intervention services, and self-reported lack of referral by a physician were the only factors that continued to be significantly correlated, and in fact, the truly influential ones associated with number of attending times. Conclusion: Results of this study have defined some predictors of poor follow up and early intervention service utilization in a high-risk group of infants following NICU discharge, which is suggested to be addressed by policymakers to overcome possible barriers to attendance.